(Ne)privlačnosti z vidika življenja in dela na podeželju - Potočnik Slavič, Irma (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2019)
Our research focused on the spatial distribution of amenity and disamenity attribu-tes affecting living and working conditions in a demographically and economically dynamic rural area with good transport connections. In this article, the concept of amenity is defined as the quality(-ies)/characteristics of a rural place that make it appealing for people to reside and work in, not only in terms of quantitative aspects but also dependent on individuals' perceptions. We tested detecting such (dis)amenity attributes in Dežela (the north-western part of the Ljubljana Basin) with two target groups - geography students and local residents, while also comparing the results obtained via classical fieldwork and through collaborative mapping. We found that the responses of geography students and local residents in the study area were generally consistent both in terms of content and location. It would be sensible to take these results into consideration during the preparation of development documents (local development strategy, tourism development strategy). Use of collaborative mapping methods, along with diligent planning and clearly defined goals, enabled us to simplify the data collection process and involve younger portions of the population, who generally are not sufficiently engaged in planning processes.
Keywords: amenity; Dežela; disamenity; Gorenjska; kartiranje; mapping; podeželje; razvoj podeželja; regionalni razvoj; rural areas; Slovenia; Slovenija